EFFECT OF EIGHT HOURS PER DAY OF INTERMITTENT SELF-PRONE POSITIONING FOR SEVEN DAYS ON THE SEVERITY OF COVID-19 PNEUMONIA/ ACUTE RESPIRATORY DISTRESS SYNDROME - Javed, Hamza; Qayyum, Fatima; Khan, Muhammad Naushad Aslam; Ashraf, Mubashra; Elahi, Awais; Hayat, Haseeb; Khan, Sameed; Malik, Sidra Qayyum; Amanullah, Khadija (Journal of Ayub Medical College Abbottabad, 2023)
Background: Prone positioning improves ventilation-perfusion mismatch, distribution of gravitational gradient in pleural pressure, and oxygen saturation significantly in patients with Covid pneumonia. We aimed to find out the efficacy of eight hours per day of intermittent self-prone positioning for seven days in patients affected with COVID-19 pneumonia/ ARDS. Methods: This Randomized Clinical Trial was conducted in the Covid isolation wards of Ayub Teaching Hospital, Abbottabad. Patients suffering from COVID-19 pneumonia/ ARDS were enrolled with permuted block randomization into a control and an experimental group each consisting of 36 patients. Parameters of Pneumonia Severity Index (PSI) score along with other sociodemographic data was noted on a preformed structured questionnaire. Death was confirmed by requesting the death certificate of patients on the 90th day of enrolment. Data Analysis was done with SPSS Version 25. Tests of significance were applied to calculate the difference in the patients of the two groups with respect to respiratory physiology and survival. Results: The mean age of the patients was 63.79±15.26 years. A total of 25 (32.9%) male and 47 (61.8%) female patients were enrolled. Statistically significant improvement was found in the respiratory physiology of the patients at 7th and 14th DOA between the groups. Pearson Chi-Square test of significance showed a difference in mortality between the two groups at 14th DOA (p-value=0.011) but not at 90th DOA (p-value=0.478). Log Rank (Mantel-Cox) test of significance, applied on the Kaplan Meier curve and showed no statistically significant difference among the groups based on the survival of the patients. (p-value=0.349). Conclusion: Early transient improvement in respiratory physiology and mortality does occur with 8 hours of self-prone positioning for seven days but there is no effect on the 90-day survival of the patients. Thus, the impact of the manoeuvre on improving survival needs to be explored with studies having an application of the manoeuvre for a longer duration and period.